A study on the compressive strength and microstructure characteristic of alkali-activated metakaolin cement - Karatas, Mehmet; Dener, Murat; Mohabbi, Mehrzad; Benli, Ahmet (Univ Fed Rio de Janeiro, Lab Hidrogenio, 2019)
The main purpose of this study was to investigate the compressive strength and microstructure characteristic of alkali-activated metakaolin cement (AAMC). In accordance with this purpose, besides the pure metakaolin activation five other mixtures were designed by substitution of different OPC ratios instead of metakaolin (MK) from 0 to 25 (5, 10, 15, 20, 25% OPC). AAMC was activated with sodium silicate (Na2SiO3) of modulus Ms = SiO2/Na2O = 3.1 and NaOH solutions (32% of NaOH, 68% of water by mass). The ratio of liquid/solid (L/S) was kept constant at 0.65. All specimens were cured at 70 degrees C for 72 hours then kept in room conditions until the days that experiments were performed. Compressive strength and UPV experiment tests were carried out on all specimens at different curing periods of 3,14,28 and 90 days. In addition, the microstructure of 28 days alkali-activated metakaolin cements were analyzed with scanning electron microscope (SEM). The results showed that AAMC specimens reached the desired strength and major part of the final strength was gained at the end of 3 days of curing.
Keywords: Alkali activated cement; Geopolymer; Metakaolin; microstructure; UPV